2021
DOI: 10.1007/s12031-021-01944-1
|View full text |Cite
|
Sign up to set email alerts
|

Intercellular Propagation and Aggregate Seeding of Mutant Ataxin-1

Abstract: Intercellular propagation of aggregated protein inclusions along actin-based tunneling nanotubes (TNTs) has been reported as a means of pathogenic spread in Alzheimer’s, Parkinson’s, and Huntington’s diseases. Propagation of oligomeric-structured polyglutamine-expanded ataxin-1 (Atxn1[154Q]) has been reported in the cerebellum of a Spinocerebellar ataxia type 1 (SCA1) knock-in mouse to correlate with disease propagation. In this study, we investigated whether a physiologically relevant polyglutamine-expanded A… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…One previous report inferred Wallerian degeneration between the cerebellum and brainstem in SCA2 patients. 27 Another possible explanation for this is the involvement of the intercellular propagation of abnormal polyglutamineexpanded proteins, which has been reported in other polyglutamine disorders such as SCA1 28 and Huntington's disease. 29 In the supratentorial brain, prefrontal cortex, amygdala, and hippocampus project specific information to the NAc.…”
Section: Discussionmentioning
confidence: 94%
“…One previous report inferred Wallerian degeneration between the cerebellum and brainstem in SCA2 patients. 27 Another possible explanation for this is the involvement of the intercellular propagation of abnormal polyglutamineexpanded proteins, which has been reported in other polyglutamine disorders such as SCA1 28 and Huntington's disease. 29 In the supratentorial brain, prefrontal cortex, amygdala, and hippocampus project specific information to the NAc.…”
Section: Discussionmentioning
confidence: 94%
“…Despite tempting links to other repeat expansion disorders like HD, there remains controversy surrounding the mechanisms of many SCA disorders. , For SCA-1, questions persist regarding whether the polyQ expansion can exit the nucleus and what drives disease pathology. , Other SCAs associated with ataxin polyQ expansion disorders also may not necessarily share the same disease mechanisms. , However, despite the complexity, investigating the role of RNA in the aggregation of SCA-related proteins offers a promising avenue for further research and potential treatments.…”
Section: Nucleic Acid Roles In Protein Aggregation Diseasesmentioning
confidence: 99%
“…189−191 SCA type 1 (SCA1), the first well-characterized SCA, results from CAG repeats in the ATXN1 gene, leading to a polyglutamine expansion in the ataxin-1 protein. 193,195 Ataxin-1 is a gene repressor and functions primarily as a DNA-binding protein, although it can also interact with RNA. 196,197 Studies using ataxin-1 with varying polyQ repeat lengths have demonstrated its ability to bind both polyU and polyG RNA, with a stronger affinity for polyG.…”
Section: Diseasesmentioning
confidence: 99%
See 2 more Smart Citations